Condition audit and maintenance for public building (Police Quarters) / Mohd Nor Rashidee Nora Afandi - Nora Afandi, Mohd Nor Rashidee (Faculty of Architecture, Planning and Surveying, 2010)
Building maintenance is very important in a placement or an area. It is ensuring the life healthy ones and harmony achievable due to building in which case in good. In fact building that well groomed necessarily become choice for population so that they felting safe to stay. Accordingly, maintenance was of paramount importance in safeguarding asset from problem. To know about problems and so on maintenance, 4 Case studies was elected according to field study topic. Case study is made under supervise PDRM (Polis DiRaja Malaysia). The area that studied is under Shah Alam district and Klang district and focussed in managing and problem that faced by building and population. In providing dissertation, there will study on the maintenance of the police quarters and there will be brief condition audit to know building condition and problem that there are in building that maintained by officers that responsible by PDRM. Additionally, author should also know public satisfaction on the problem of encountering. Lastly, some suggestions proposed to overcome those problems emerges in management and some suggestions also been given in improving maintenance management quality in building quarters police.